2015
DOI: 10.1002/adma.201503367
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Synthesis of Organic/Inorganic van der Waals Solid for Tunable Light–Matter Interactions

Abstract: High-quality organic and inorganic van der Waals (vdW) solids are realized using methylammonium lead halide (CH3 NH3 PbI3 ) as the organic part (organic perovskite) and 2D inorganic monolayers as counterparts. By stacking on various 2D monolayers, the vdW solids exhibit dramatically different light emissions. Futhermore, organic/h-BN vdW solid arrays are patterned for red-light emission.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
127
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 120 publications
(130 citation statements)
references
References 51 publications
2
127
0
1
Order By: Relevance
“…This indicates a high level of phase purity for the hexagonal crystal structure of PbI 2 which has a highly oriented growth direction along the c‐axis. After conversion, CH 3 NH 3 PbI 3 with a tetragonal crystal structure were formed – evident from the characteristic peaks at 14.06°, 28.38°, 31.74°, and 43.14°, which are assigned to (110), (220), (310), and (330) for pure CH 3 NH 3 PbI 3 crystals, respectively 28. From Raman measurements, PbI 2 and CH 3 NH 3 PbI 3 possess almost the same Raman spectra (Figure 2b) indicating that the perovskite platelet retains the 4H polytype of PbI 2 38.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This indicates a high level of phase purity for the hexagonal crystal structure of PbI 2 which has a highly oriented growth direction along the c‐axis. After conversion, CH 3 NH 3 PbI 3 with a tetragonal crystal structure were formed – evident from the characteristic peaks at 14.06°, 28.38°, 31.74°, and 43.14°, which are assigned to (110), (220), (310), and (330) for pure CH 3 NH 3 PbI 3 crystals, respectively 28. From Raman measurements, PbI 2 and CH 3 NH 3 PbI 3 possess almost the same Raman spectra (Figure 2b) indicating that the perovskite platelet retains the 4H polytype of PbI 2 38.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, Zhu et al recently reported a solution‐processed technique to synthesize single‐crystal perovskite nanowires and demonstrated their application on lasers with high‐quality factor and low lasing threshold 26. However, few works focus on the following two highly important features: (i) finding a straightforward means for selective or directed and/or periodic placement of perovskite micro/nanostructures; and (ii) the compatibility of substrates on which perovskite structures were grown for further optoelectronic integration 27, 28. Consequently, controlled growth or pattering of these perovskite building blocks on the ubiquitous silicon optoelectronics platform is a crucial step toward realization of practical optoelectronic devices.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2g, based on which lattice patterns of the MAPbBr 3 [001]-zone axis and MoS 2 [001]-zone axis were re-generated and shown in Fig. 2h, [32]. In that case, both PbI 2 and the 2D material exhibited the six-fold symmetry at the heterointerface.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, colloidal NCs with small lateral sizes suffer from poor film-forming ability, restricting their use in applications where continuous films for charge transporting are required. Recently, TMDs and organic-inorganic hybrid perovskites have been combined into heterostructures, with the aim to marrying their good electronic and optical properties [32][33][34][35][36][37]. For example, photoconductors based on WSe 2 / CH 3 NH 3 PbI 3 [34] and WS 2 /CH 3 NH 3 PbI 3 [35] demonstrated superior photo-responsive performance compared to single-component devices.…”
Section: Introductionmentioning
confidence: 99%